Impact of different road types on small mammals in Mt. Kalamaili Nature Reserve. (January 2017) - Ji, Shengnan; Jiang, Zhigang; Li, Lili; Li, Chunwang; Zhang, Yongjun; Ren, Shien; Ping, Xiaoge; Cui, Shaopeng; Chu, Hongjun
Highlights: Assessing how different types of roads affect the movement of small mammals. Life history or microhabitat preferences could predict animals' responses to roads. The results can give recommendations for animal conservation in road construction. Abstract: Understanding how roads affect connectivity of wildlife populations is one of the challenges in road ecology. Road avoidance behavior in animals may fragment populations, whereas lacking of road avoidance behavior in animals presumably result in high mortality due to wildlife-vehicle collisions. Small mammals are of great interest on account of their value as indicators of environmental impacts and their key role in ecosystems. Applying mark-recapture method, we conducted trapping experiment and artificial translocation to assess how different types of roads affect the small mammals in Mt. Kalamaili Nature Reserve in northern Xinjiang, China. The results show that of the two small mammal species that were most commonly trapped, the abundance of great gerbils ( Rhombomys opimus ) increased near unpaved road and decreased at paved road sites, as opposed to Mongolian five-toed jerboas ( Allactaga sibirica ); road crossing events of great gerbils were primarily influenced by the paved road, rather than the unpaved road, in contrast to Mongolian five-toed jerboas were unaffected by road types (no matter paved- or unpaved roads). Therefore, our results indicated that great gerbils avoided paved road, while paved road had no influence on Mongolian five-toed jerboas. The interspecific difference implied that microhabitat use preferences, life-history strategies and road substrate help to predict how species responses to barrier of different road types, but traffic volume may have little effect. However, since higher traffic levels were not coincided with the peak periods for activity of the nocturnal species, further investigations are needed to be continued.